A Dyadic Analysis of Depressive Symptoms, Harsh Parenting, and Rejection in Filipino Mothers and Fathers - Jocson, Rosanne M (Archīum Ateneo, 2020)
This study examines within-person and cross-person relations between depressive symptoms, harsh parenting, and parental rejection in low-income Filipino mothers and fathers of adolescents using an actor–partner interdependence model (APIM). Mother and father dyads (N = 81, Mage = 43.48, SD = 8.66) recruited from urban neighborhoods in the Philippines completed orally administered questionnaires on depressive symptoms, harsh parenting, and rejection. Results showed that mothers' scores and fathers' scores on depressive symptoms did not significantly differ and that mothers scored significantly higher than fathers on harsh parenting and rejection. Dyadic analyses using the APIM showed that the actor effect of depressive symptoms on harsh parenting was statistically significant for fathers only and that the actor effects of depressive symptoms on rejection were statistically significant for both mothers and fathers. No partner effects on harsh parenting and rejection were statistically significant. These findings contribute to the robust evidence linking parental depressive symptoms to negative parenting behaviors and highlight the need to attend to both fathers' psychological health and mothers' psychological health in efforts to reduce harsh and rejecting parenting behaviors among Filipino parents.